2009
DOI: 10.1098/rspb.2008.1912
|View full text |Cite
|
Sign up to set email alerts
|

Birth season glucocorticoids are related to the presence of infants in sifaka ( Propithecus verreauxi )

Abstract: The responses of plural breeding mammals to environmental stressors are little understood in free-ranging populations, but recent studies of singular breeders suggest that ecological factors and social milieu influence the variable physiological stress responses observed among individuals. Our previous studies examining faecal glucocorticoid (fGC)-behaviour interactions in plural breeding male sifaka (Propithecus verreauxi ) show that fGC elevations coincide with specific dispersal events, particularly the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Elevations in fCORT levels prior to becoming alpha could be linked with increased metabolic demands in preparation for aggressively taking over the alpha position; however, this is improbable because CY did not aggressively overthrow male CB (based on our observations). A more likely explanation is that CY's heightened fCORT levels were in response to his recent immigration into the group, and his increased spatial proximity to unknown individuals may have been stressful to him, as has also been observed in newly immigrant chacma baboons and sifakas [Bergman et al, 2005;Brockman et al, 2009]. While CY's fCORT did not increase immediately following his rise to alpha male (phase 2), it did increase in phases 3 and 4 to levels significantly greater than subordinate male WW.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Elevations in fCORT levels prior to becoming alpha could be linked with increased metabolic demands in preparation for aggressively taking over the alpha position; however, this is improbable because CY did not aggressively overthrow male CB (based on our observations). A more likely explanation is that CY's heightened fCORT levels were in response to his recent immigration into the group, and his increased spatial proximity to unknown individuals may have been stressful to him, as has also been observed in newly immigrant chacma baboons and sifakas [Bergman et al, 2005;Brockman et al, 2009]. While CY's fCORT did not increase immediately following his rise to alpha male (phase 2), it did increase in phases 3 and 4 to levels significantly greater than subordinate male WW.…”
Section: Discussionmentioning
confidence: 75%
“…Sifaka males (P. verreauxi) who transferred aggressively into new groups had higher testosterone levels than those who entered peacefully [Brockman et al, 2001]. However, regardless of the presence or absence of aggression, all immigrating male sifakas had elevated testosterone levels, though they decreased a few days after immigration [Brockman et al, 2001[Brockman et al, , 2009.…”
Section: Discussionmentioning
confidence: 91%
“…At Beza Mahafaly Special Reserve (BMSR), approximately one third of male transfers occur during the birth season [Brockman et al, 2001], though extra-group and peripheral males ["wanderers": Richard et al, 1993;"roamers": Kappeler and Fichtel, 2012;"floaters": Port et al, 2012] are observed more often during the mating season [Richard, 1974;Lewis, 2004]. Males sometimes travel and immigrate into groups as pairs [Jolly et al, 1982;Richard et al, 1993;Brockman et al, 2009;Kappeler and Fichtel, 2012], and transferring males rarely reside more than two home ranges away from their group of origin [Richard et al, 1993[Richard et al, , 2002. Changes in dominant male membership can occur via aggressive takeovers [Brockman et al, 2001;Kappeler et al, 2009], and male immigrations have been linked to infanticide [Brockman et al, 2001[Brockman et al, , 2009Lewis et al, 2003;Littlefield, 2010].…”
Section: Introductionmentioning
confidence: 97%
“…Males sometimes travel and immigrate into groups as pairs [Jolly et al, 1982;Richard et al, 1993;Brockman et al, 2009;Kappeler and Fichtel, 2012], and transferring males rarely reside more than two home ranges away from their group of origin [Richard et al, 1993[Richard et al, , 2002. Changes in dominant male membership can occur via aggressive takeovers [Brockman et al, 2001;Kappeler et al, 2009], and male immigrations have been linked to infanticide [Brockman et al, 2001[Brockman et al, , 2009Lewis et al, 2003;Littlefield, 2010]. Competition among males for group vacancies can be extremely intense [Port et al, 2012] with extended bouts of chasing associated with immigration attempts [Richard, 1992].…”
Section: Introductionmentioning
confidence: 98%
“…Advances in field methodology have permitted collection of ancillary (nonbehavioral) data to further test the hypothesis. For example, DNA data establish that males are unrelated to the infants they attack (Pereira and Weiss 1991;Borries et al 1999a;Soltis et al 2000) or are fathers of the female's next infant (Morelli et al 2009), whereas hormonal data provide direct evidence of maternal resumption of ovulatory cycling following infanticide (Harris and Monfort 2003) as well as elevated stress response in mothers following heightened infanticide risk or actual attacks (Beehner et al 2005; see also Brockman et al 2009). Thus, as a general explanation of infanticide, the sexual selection hypotheses has received more support than alternative hypotheses (see below) (van Schaik 2000a;Palombit 2012).…”
Section: Sexual Selection Hypothesismentioning
confidence: 99%